Low high-density lipoprotein level is correlated with the severity of COVID-19 patients: an observational study - Guyi Wang; Quan Zhang; Xianmei Zhao; Haiyun Dong; Chenfang Wu; Fang Wu; Bo Yu; Jianlei Lv; Siye Zhang; Guobao Wu; Shangjie Wu; Xiaolei Wang; et al. (Lipids in Health and Disease, 2020)
Abstract Background The purpose of the study is to describe the blood lipid levels of patients diagnosed with coronavirus disease 2019 (COVID-19) and to analyze the correlation between blood lipid levels and the prognosis of COVID-19 patients. Methods In the clinical retrospective analysis, a total of 228 adults infected with COVID-19 were enrolled between January 17, 2020 and March 14, 2020, in Changsha, China. One thousand one hundred and forty healthy participants with matched age and gender were used as control. Median with interquartile range and Mann-Whitney test were adopted to describe and analyze clinical data. The Kaplan-Meier (KM) curve and Cox regression analysis were used to analyze the correlation between high-density lipoprotein cholesterol (HDL-C) and the severity of COVID-19. Results Compared with control, COVID-19 patients showed significantly lower levels of total cholesterol (TC) [median, 3.76 vs 4.65 mmol/L, P = 0.031], triglyceride [median, 1.08 vs 1.21 mmol/L, P <  0.001], low-density lipoprotein cholesterol (LDL-C) [median, 2.63 vs 2.83 mmol/L, P <  0.001], and HDL-C [median, 0.78 vs 1.37 mmol/L, P <  0.001], while compared with non-severe patients, severe COVID-19 patients only presented lower levels of HDL-C [median, 0.69 vs 0.79 mmol/L, P = 0.032]. In comparison with patients with high HDL-C, patients with low HDL-C showed a higher proportion of male (69.57% vs 45.60%, P = 0.004), higher levels of C-reactive protein (CRP) (median, 27.83 vs 12.56 mg/L, P <  0.001) and higher proportion of severe events (36.96% vs 14.84%, P = 0.001). Moreover, patients with low HDL-C at admission showed a higher risk of developing severe events compared with those with high HDL-C (Log Rank P = 0.009). After adjusting for age, gender and underlying diseases, they still had elevated possibility of developing severe cases than those with high HDL-C (HR 2.827, 95% CI 1.190–6.714, P = 0.019). Conclusions HDL-C level was lower in COVID-19 adult patients, and low HDL-C in COVID-19 patients was correlated with a higher risk of developing severe events.